2018
DOI: 10.1039/c8nr02508h
|View full text |Cite
|
Sign up to set email alerts
|

A facile approach for preparing densely-packed individual p-NiO/n-Fe2O3 heterojunction nanowires for photoelectrochemical water splitting

Abstract: Innovative design of electrode materials is crucial for efficient conversion of solar energy into chemical fuel through photoelectrochemical (PEC) water splitting. Herein, we report the development of a p-n heterojunction nanowire (NW) based photoanode made of low cost earth-abundant materials. Densely-packed and freestanding individual p-NiO/n-Fe2O3 heterojunction NWs are fabricated through consecutive electrodeposition of Fe and Ni NWs inside the pores of the anodic alumina template followed by controlled ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 45 publications
1
33
0
Order By: Relevance
“…Recently, Singh and Sarkar report the design of p-NiO/n-Fe 2 O 3 materials, which is a p-n heterojunction nanowire based photoanode (Figure 9A). [95] Compared to the original Fe 2 O 3 nanowire electrode, these p-NiO/n-Fe 2 O 3 heterojunction nanowires indicate a greatly enhanced photocurrent density (≈24 times at a potential of 1.23 V vs RHE) and a cathodic shift of the photocurrent onset potential (≈0.4 V). This is due to the synergistic combination of n-Fe 2 O 3 with the cocatalyst p-NiO, which promotes the generation of photogenerated holes and transfer to the electrolyte for water oxidation.…”
Section: Recent Progress On Ni/fe-based Catalysts For Pec Water Oxidamentioning
confidence: 89%
See 1 more Smart Citation
“…Recently, Singh and Sarkar report the design of p-NiO/n-Fe 2 O 3 materials, which is a p-n heterojunction nanowire based photoanode (Figure 9A). [95] Compared to the original Fe 2 O 3 nanowire electrode, these p-NiO/n-Fe 2 O 3 heterojunction nanowires indicate a greatly enhanced photocurrent density (≈24 times at a potential of 1.23 V vs RHE) and a cathodic shift of the photocurrent onset potential (≈0.4 V). This is due to the synergistic combination of n-Fe 2 O 3 with the cocatalyst p-NiO, which promotes the generation of photogenerated holes and transfer to the electrolyte for water oxidation.…”
Section: Recent Progress On Ni/fe-based Catalysts For Pec Water Oxidamentioning
confidence: 89%
“…Reproduced with permission. [95] Copyright 2018, The Royal Society of Chemistry. B) Schematic of the one-step hydrothermal process for depositing Ni:FeOOH OECs on anisotropic nanostructures, such as WO 3 /BiVO 4 core/shell nanowires.…”
Section: Discussionmentioning
confidence: 99%
“…[30] Sarkar and Singh reported that the axial junction of p-NiO x /n-Fe 2 O 3 significantly enhanced the photocurrent density and resulted in cathodic shift of the onset potential of the photocurrent. [31] Due to the formation of a p-n junction and the existence of NiO x as an OER catalyst, the time constant of the transient photocurrent of NiO x /Fe 2 O 3 was five times longer than that of bare Fe 2 O 3 , suggesting the CR was remarkably suppressed at electrode/electrolyte interface by NiO x .…”
Section: Charge Separationmentioning
confidence: 98%
“…[23] Copyright 2018, Springer Nature Publishing AG. forming a p-n junction [28][29][30][31] or a metal-insulator-semiconductor (MIS) junction [32] at the semiconductor/electrocatalyst interface.…”
Section: Charge Separationmentioning
confidence: 99%
“…Since its invention in 1972, a host of metal oxides have been explored as efficient catalysts for PEC water splitting. Among these, hematite (Fe 2 O 3 ) has drawn particular attention as a promising photo‐electrode material because of its suitable band gap for significant light absorption in the visible region of the solar spectrum, high abundance and astounding chemical stability in aqueous electrolytes . However, it's performance is critically limited by a very short hole diffusion length (∼2–4 nm) and poor majority carrier conductivity which lead to recombination losses of photogenerated charge carriers in the bulk .…”
Section: Introductionmentioning
confidence: 99%